Evaluation of Immunomodulatory Effect of a Novel Test Formulation in D-Galactose-Induced Aging Dysfunction in Sprague Dawley Rats - Kumar Trivedi Mahendra; Branton Alice; Trivedi Dahryn; Jana Snehasis (Journal of Aging Research And Healthcare, 2021)
The aim of the study was to evaluate the immunomodulatory activity of the Biofield Treated/Blessed proprietary test formulation consisting of essential ingredients viz. minerals (zinc, magnesium, iron, and copper) and vitamins (B6, B12, and D3) in male Sprague Dawley rats. Each ingredient of the test formulation was divided into two parts. One part was denoted as the control without any Biofield Energy Healing Treatment/Blessing, while the other part was defined as the Biofield Energy Treated/Blessed sample, which received the Biofield Energy Healing Treatment/Blessing by a renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi remotely. Additionally, three group of animals were also received Biofield Energy Treatment per se (at day -15) under similar conditions. The parameters were assessed such as immune biomarkers (IgM, IgG, IgA, IgE, CD4+, CD8+, and CD28+), biochemistry and hematology and histopathology. The experimental results showed IgG level was significantly increased by 10.70% and 8.03% in the G6 (Biofield Energy Treatment per se at day -15) and G8 (Biofield Treatment per se to animals plus Biofield Treated test formulation from day -15) groups, respectively as compared with untreated test formulation (G4). Additionally, CD8+ count was significantly increased by 20.67% in the G8 group, while CD28+ count was significantly increased by 11.70%, 8.32%, and 9.82% in the G7 (Biofield Energy Treated test formulation at day -15), G8, and G9 (Biofield Treatment per se (day -15) to animals plus untreated test formulation) groups, respectively after Biofield Energy Treatment to the animals as compared with the untreated test formulation. In hematological analysis, platelet count was increased in the G5, G6, G7, G8, and G9 groups by 40.69%, 27.95%, 26.67%, 38.58%, and 28.28%, respectively compared with the disease control (G2) group. Biochemical parameters showed significant decrease in the level of creatinine by 32.14% in the G9 group as compared with the G2 group. Further, animal body weight, feed intake, relative organ weight, and histopathological findings of all the tested groups did not show any abnormal findings with respect to the safe and non-toxic treatment strategies. Overall, the experimental data concluded that the Biofield Energy Treated/Blessed test formulation showed considerable improved cellular and humoral immune response as compared with the untreated test formulation. Thus, the Trivedi Effect®-Biofield Energy Healing Treatment per se and the test formulation has the significant capacity for immunomodulatory effect, stress management and anti-aging by improving overall health.
Keywords: Biofield Energy Healing Treatment